Informative indices of physical and functional state of young men during the process of adaptation to learning - O.V. Tulyakova; M.S. Avdeeva (H.S. Skovoroda Kharkov National Pedagogical University, 2018)
Purpose: to determine indicators of physical development, physical readiness, functional condition of young men in the process of adaptation to learning. Material: The students of university (n=78, age 18-20 years) were examined. An examination was conducted at the beginning of the first and second years of study. It was studied 8 indexes and 5 indexes for physical development. Result: it is established that during the first year of study there is an increase in: weight-growth indices; endurance factor; adaptive capacity; diastolic pressure; running record on 1000 m. The vital capacity of the lungs decreased; life index; time of hanging on a bar. Conclusions: indicators of students' adaptation to learning are suggested to be: body mass index (physical development index); running on 1000 m (the indicator of physical readiness); coefficient of endurance (indicator of functional state).